Advancing cardiac motion estimation with emerging AI techniques for enhanced echocardiographic image registration - M. Rajesh; S. Balakrishnan; R. Elankavi (MethodsX)
Monitoring and diagnosis of cardiovascular diseases rely on cardiac motion estimation. The methods used for registering echocardiographic images have drawbacks such as low resolution, noise, and distortion of the anatomy. In order to enhance the prediction of cardiac motion, this research presents an AI-powered architecture that makes use of Vision Transformers, Diffusion Models, and Neural Radiance Fields (NeRF). Adversarial and self-supervised contrastive learning enhance picture quality and generalisability across adult and foetal echocardiography, while a graph neural network (GNN)-based anatomical constraint maintains heart shape. Better, more accurate, more efficient real-time motion tracking without relying on massive labelled datasets is possible with the proposed approach. Cardiac motion analysis in a wide range of patient populations is now therapeutically viable, thanks to this innovative approach that improves echocardiographic picture registration. • Utilizes Vision Transformers, Diffusion Models, and NeRF for high-quality cardiac motion prediction. • Adversarial and self-supervised contrastive learning improve echocardiographic registration across demographics. • A GNN-based anatomical constraint ensures accurate heart morphology during motion analysis.